2017
DOI: 10.1021/acs.nanolett.7b00189
|View full text |Cite
|
Sign up to set email alerts
|

Human Immune Protein C1q Selectively Disaggregates Carbon Nanotubes

Abstract: We atomistically compute the change in free energy upon binding of the globular domain of the complement protein C1q to carbon nanotubes (CNTs) and graphene in solution. Our modeling results imply that C1q is able to disaggregate and disperse bundles of large diameter multiwalled CNTs but not those of thin single-walled CNTs, and we validate this prediction with experimental observations. The results support the view of a strong binding with potential implications for the understanding of the immune response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Several studies have shown that C1q binds to nanomaterial surfaces, though this binding does not necessarily lead to complement activation [reviewed in (7)]. Recent modeling studies suggested that C1q is able to disaggregate bundles of multi-walled CNTs, but not those of thin, single-walled CNTs and these predictions were validated with experimental observations (45). These findings may be relevant for the toxicity of CNTs irrespective of whether or not complement is activated, as the (pulmonary) toxicity of CNTs was suggested to be attributable to aggregation of the CNTs rather than the high aspect ratio of individual nanotubes (46).…”
Section: Immune Evasionmentioning
confidence: 88%
“…Several studies have shown that C1q binds to nanomaterial surfaces, though this binding does not necessarily lead to complement activation [reviewed in (7)]. Recent modeling studies suggested that C1q is able to disaggregate bundles of multi-walled CNTs, but not those of thin, single-walled CNTs and these predictions were validated with experimental observations (45). These findings may be relevant for the toxicity of CNTs irrespective of whether or not complement is activated, as the (pulmonary) toxicity of CNTs was suggested to be attributable to aggregation of the CNTs rather than the high aspect ratio of individual nanotubes (46).…”
Section: Immune Evasionmentioning
confidence: 88%
“…A more recent simulation study, supported by experimental results, does also suggest that a globular protein may also disaggregate large bundles of multi-walled CNT with a large diameter, but not the single-walled CNT with a small diameter [16]. The chosen protein was a globular domain of C1q, a large multifunctional protein formed by six well separated globular domains, gC1q, each connected to a collagen stem that eventually form a single fibril.…”
Section: Carbon Nanotubes (Cnt)mentioning
confidence: 86%
“…Chiral CNT are characterized by (n, m) indices with n s m: in chemical terms, enantiomeric chiral nanotubes have swapped indices (n, m) and (m, n), and can interact with chiral molecules such as the oligopeptides forming in principle complexes with an unlike stability. The selected CNT were the (10,20) and the (20, 10) CNT with a diameter of 2.07 nm, while an armchair (16,16) CNTwith a very similar diameter was also considered for a comparison. The MD simulations, carried out in an implicit solvent, considered four starting oligopeptide orientations close the outer CNT convex surface, and other four ones close to the CNT open end, but outside the inner cavity, to model adsorption on the concave surface if encapsulation took place in the MD run.…”
Section: Graphene and Graphynementioning
confidence: 99%
“…If it is necessary to handle nanoparticle powders outside of a high-efficiency particulate air filtered to maintain exhaust streamline flow hood. Lab equipment and exhaust systems should also be evaluated before removal, remodeling, or repair [26,27]. Given the differing artificial ways and experimental goals, no blanket recommendation will be created concerning aerosol emissions controls.…”
Section: Strategy For Functioning With Nanomaterialsmentioning
confidence: 99%